Estudo dos possíveis mecanismos da ação hipoglicemiante da pentoxifilina no modelo de diabetes Mellitus induzido por aloxano em ratos - Garcia, Francisca Adilfa de Oliveira (2012)
Pentoxifylline (PTX) is a non-selective inhibitor of phosphodiesterase with anti-inflammatory vascular and rheological properties. The drug can neutralize some of the changes seen in diabetes mellitus (DM), contributing to attenuate diabetes secondary complications as neuropathy, retinopathy and nephropathy. Considering PTX anti-inflammatory properties and the known involvement of inflammation with DM, we investigated its possible hypoglycemic and hypolipidemic effects in the model of alloxan-induced DM in rats. Pentoxifylline pilot studies in reduced plasma levels of glucose and triglycerides in animals with diabetes induced by alloxan at the doses of 5, 25, 50 and 100 mg/kg. Oral administration of the combination of PTX with glibenclamide (GLI), PTX5 + GLI2, caused significant reductions in plasma levels of glucose and triglycerides in the short and long term, indicating that the mechanism of action of PTX can be explained via K+ATP-dependent channels. The oral administration of the combination of pentoxifylline (PTX) with metformin (MET), PTX5+MET5, caused a reduction of only the long term hyperglycemia, suggesting that these two drugs do not share the same mechanism. PTX did not block the hyperglycemia induced by diazoxide (DZD), an antagonist of GLI, which inhibits insulin secretion by prolonging the opening time of the K+ATP-dependent-channel. This result suggests that other factors, in addition to the blockade of the K+ATP dependent channels, may be involved. The reduction in glycosylated hemoglobin (A1C), and fructosamine showed that treatment with the combination PTX5+GLI2 and PTX50, improved glycemia in the study, indicating that this drug can inhibit the development of macrovascular and microvascular injury resulting from DM. The PTX showed a marked anti-inflammatory effect, improving the general condition of rats subjected to acute inflammation models. PTX reduced significantly, the paw edema at doses of 50 and 100 mg / kg, However, the inflammatory profile in diabetic rats have a different pattern of that seen in non-diabetic rat, showing an amplification of the inflammatory process. We showed that the levels of TNF-α and IL-6 were significantly increased after the induction of paw edema in diabetic rats, but in the rats treated with PTX tissue levels of these cytokines were significantly lower, which indicating a clear anti-inflammatory action of PTX. PTX also showed a significant antioxidant effect reducing significantly the release of tissue and serum nitrite, acting favorably in the reduction of free radicals. The prolonged treatment with PTX was effective in maintaining the normal histological pattern of the pancreas, liver and kidneys in diabetic groups treated with PTX50 PTX5 + and GLI2, indicating a protective effect of PTX against alloxan-induced cytotoxicity. The hypoglycemic and hypotriglyceridemic effects of PTX, shown here, may correlate with its effect on oxidative stress and on low grade inflammation, making PTX an important candidate for the management of diabetes mellitus in the clinic.